Влияние пыли перегружаемых в портах опасных навалочных грузов на санитарно-экологическое состояния почв припортовых городов причерноморья = Influence of dust transferred into ports of dangerous cargos for bulk sanitary-ecological condition of soils port urban Black Sea - Belobrov, E. P.; Zambriborshch, M. S.; Sidorenko, S. G.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Belobrov E. P., Zambriborshch M. S., Sidorenko S. G., Zukow W. Влияние пыли перегружаемых в портах опасных навалочных грузов на санитарно-экологическое состояния почв припортовых городов причерноморья = Influence of dust transferred into ports of dangerous cargos for bulk sanitary-ecological condition of soils port urban Black Sea. Journal of Education, Health and Sport. 2015;5(7):604-619. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.62038 http://ojs.ukw.edu.pl/index.php/johs/article/view/3847 Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. Влияние пыли перегружаемых в портах опасных навалочных грузов на санитарно-экологическое состояния почв припортовых городов Причерноморья Е. П. Белобров, М. С. Замбриборщ, *С. Г. Сидоренко, **В. А. Жуков Украинский НИИ медицины транспорта Минздрава Украины, Одесса *Главное управление Госсанэпидслужбы в Кировоградской области, Кировоград **UKW, Bydgoszcz, Poland Реферат Почва является одним из основных концентраторов химических загрязняющих веществ, включая тяжелые металлы, которые при избыточном содержании проявляют свои токсические свойства. Они являются генетическими ядами, поскольку, попадая в организм, аккумулируются с отдаленным эффектом действия. Одним из наиболее токсичных металлов является свинец, данный элемент относится к первому классу опасности. Авторы провели санитарно-экологическую оценку состояния почв прибрежно-береговых территорий в условиях воздействия пыли навалочных грузов, перегружаемых в морских портах Одесского региона – Ильичевска, Одессы, Южного. Пыль различных грузов представляет потенциальную опасность, которую необходимо учитывать при проведении перегрузочных работ. Кроме того, разница в агрегатном состоянии дисперсных частиц, влажности и других физико-химических характеристик имеют не только технологическое, но и эколого-геохимическое значение для почв. Так как большинство вредных примесей и компонентов находятся в аэрозольной фазе, для предупреждения пылеобразования следует учитывать процентное содержание пылевой фракции в грузах. Изучение почв и их химического состава в районах активных перевалочно-насыпных работ на территории, прилегающей к портам городов Одессы, Южного и Ильичевска, показало, что происходит аккумулирование тяжелых металлов и других загрязняющих элементов и веществ в верхних слоях почвы, что ведет к повышению экологической нагрузки на почву. Ключевые слова: почва, припортовые территории, тяжелые металлы, опасные грузы INFLUENCE OF DUST transferred into PORTS OF DANGEROUS cargoS FOR BULK sanitary-ecological condition of soils Port URBAN BLACK SEA E. P. Belobrov, M. S. Zambriborshch, *S. G. Sidorenko, **W. Zukow Ukrainian Scientific Research Institute of Transport Medicine of Ministry of Health of Ukraine, Odessa *General Directorate GosSanEpidemNadzor in Kirovograd region, Kirovograd **KWU, Bydgoszcz, Poland Abstract Soil is one of the main hubs of chemical contaminants, including heavy metals, which when excessive content exert their toxic properties. They are genetic poisons, because getting into the body, with accumulated long-term effects of action. One of the toxic metal is lead, the element belongs to the first class of hazard. The authors conducted a sanitary and environmental assessment of soil-shore coastal areas under the impact of dust bulk cargo transhipped at sea ports ofOdessaregion - Ilyichevsk,Odessa, Southern. Dust various cargoes is a potential danger that must be taken into account during the transfer operations. In addition, the difference in the state of aggregation of dispersed particles, humidity and other physical and chemical characteristics are not only technological, but also ecological and geochemical significance for soil. Since most of the impurities and harmful components are in phase, aerosol, to prevent dust formation should be considered dust fraction percentage in loads. The study of soils and their chemical composition in areas of active transshipment and bulk of work on the territory adjacent to the port city of Odessa, the Southern and Ilyichevsk, has shown that there is accumulation of heavy metals and other polluting elements and substances in the upper layers of the soil, which leads to an increase in the environmental load soil. Keywords: soil, territory near ports, heavy metals, dangerous cargos